Desenvolvimento de um criogel de troca iônica para captura das proteínas das folhas da ora-pro-nobis (Pereskia aculeata Miller) - Mendes, Mariana Oliveira (2022)
The development of new macroporous adsorbent matrices that allow separating and purifying molecules while maintaining their bioactivity has aroused the interest of many researchers. In this context, several researches explored the potential of application of purified proteins in several sectors. Ora-pro-nobis (OPN) is a plant that has a rich nutritional composition, containing a high content of proteins, which are being widely used as a food additive, production of biodegradable packaging, edible films, production of biopharmaceuticals, among others. In view of the above, the objective of this work was to develop an ion-exchange cryogel for the adsorption of OPN leaf proteins (PFOPN) (Pereskia aculeata Miller). For this, the functionalization of ion exchange cryogels was performed using ammonium sulfate (2,75 mol L-1, at pH 9,5) containing the ion exchange ligands (taurine, cysteine, polyethyleneimine and glutamic acid) at 35 ºC for 20 h. Adsorption assays were carried out in batches using functionalized cryogels, which were submerged in sodium phosphate buffer (0,25 mol L-1) and OPN leaf extract at pH 2,5, 5,5 and 8,5, at 1:1 dilution concentration at 25 °C for 24 h. The Completely Randomized Design (DIC) was applied to analyze the significant differences between the effects of ligands on the adsorptive capacity. The Central Composite Rotational Design (DCCR) was used to optimize the functionalization method, where the time varied from 17 to 39 h and the temperature varied from 28 to 71 ºC, using the binder that presented the best adsorptive capacity in the adsorption test. Furthermore, the cryogels that showed the best adsorptive capacity were subjected to characterization in terms of their chemical, morphological, thermal and mechanical properties. Finally, the adsorption isotherms were determined at 8 °C, 15 °C, 25 °C and 35 °C varying the dilution proportions of OPN leaf extract and sodium phosphate buffer (0,025 mol L-1, pH 5,5) in 1:1, 1:2, 1:3, 1:4, 1:6, 1:8 and 1:10. The Langmuir and Freundlich models were fitted to the experimental data. The cryogel functionalized with glutamic acid (cryogel-AG) had the best adsorptive capacity, presenting interconnected pores ranging from 6–75 μm, swelling capacity of 14,113 ± 0,867 g g-1 and degree of expansion of 1,569 ± 0,058, good thermal and mechanical resistance, showing no significant differences in relation to pure cryogels. Among the pH values studied in the adsorption of PFOPN, at pH 5,5 the cryogel behaved as an amphoteric exchanger, presenting positive and negative surface charges. In this condition, there was a greater adsorption of PFOPN. The Langmuir and Freundlich models, adjusted to the experimental data, obtained predicted results of maximum adsorption capacity of 172,4 mg g-1 to 400,0 mg g-1 and 49,58 mg g-1 to 108,3 mg g-1, respectively. Thermodynamic analysis based on the Van't Hoff relation indicated that the process was spontaneous and entropy driven. The results show that cryogel-AG is a promising matrix for use in ion exchange protein capture processes.